Phosphoglycerate mutase 1 regulates dNTP pool and promotes homologous recombination repair in cancer cells - Jia Qu; Wenyi Sun; Jie Zhong; Hao Lv; Mingrui Zhu; Jun Xu; Nan Jin; Zuoquan Xie; Minjia Tan; Shuhai Lin; Meiyu Geng; Jian Ding; et al. (2017)
Glycolytic enzymes are known to play pivotal roles in cancer cell survival, yet their molecular mechanisms remain poorly understood. Phosphoglycerate mutase 1 (PGAM1) is an important glycolytic enzyme that coordinates glycolysis, pentose phosphate pathway, and serine biosynthesis in cancer cells. Herein, we report that PGAM1 is required for homologous recombination (HR) repair of DNA double-strand breaks (DSBs) caused by DNA-damaging agents. Mechanistically, PGAM1 facilitates DSB end resection by regulating the stability of CTBP-interacting protein (CtIP). Knockdown of PGAM1 in cancer cells accelerates CtIP degradation through deprivation of the intracellular deoxyribonucleotide triphosphate pool and associated activation of the p53/p73 pathway. Enzymatic inhibition of PGAM1 decreases CtIP protein levels, impairs HR repair, and hence sensitizes BRCA1/2-proficient breast cancer to poly(ADP-ribose) polymerase (PARP) inhibitors. Together, this study identifies a metabolically dependent function of PGAM1 in promoting HR repair and reveals a potential therapeutic opportunity for PGAM1 inhibitors in combination with PARP inhibitors.